Islamic and Conventional Banking in Malaysia Distinguishing Them Using Financial Ratios - Vijayarajan, Vishalini (2008)
At a cursory glance, Islamic banking sector seems robust and profitable, growing about 19% per annum, surpassing the 16% growth of conventional banks, according to Bank Negara Malaysia. Due to the financial liberalisation of Islamic banks, big foreign financial institutions including Citigroup, HSBC and Deutche Bank have jumped on the Islamic bandwagon either by starting Islamic windows or Islamic subsidiaries. This is in line with the liberalisation of Islamic banks which was brought forward to 2004 from 2007 by Bank Negara Malaysia. Islamic banks operate under different principles, such as risk sharing, mark up pricing and the prohibition of interest which is different from the way conventional banks operate. However both types of banks operate side by side under the dual banking framework in Malaysia and face similar competition. Therefore, this study determines whether it is possible to distinguish between conventional and Islamic banks in Malaysia by using financial characteristics alone in the period of liberalisation where competition is intense. It remains unclear whether financial ratios will defer significantly between the two categories of banks. 8 financial ratios were used as inputs into the logit classification model to determine whether researches or regulators could use these ratios to distinguish between the two types of banks. Although the means of several ratios are similar between the types of banks the logit classification model is able to distinguish an Islamic from a conventional bank at about a success rate of 61%.